Cohabitation Offences Balance Morality and Privacy in Criminal Code: Delik Kohabitasi Menyeimbangkan Moralitas dan Privasi dalam KUHP - W. Yantu, Safrizal; U. Puluhulawa, Fenty; Imran, Suwitno Yutye (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Cohabitation regulation in the National Criminal Code reflects a major transformation in criminal law reform by placing morality, marriage protection, legal certainty, and privacy within one normative framework. Specific Background Articles 411–412 regulate sexual intercourse outside marriage and living together as husband and wife outside a valid marriage, while positioning both provisions as complaint-based offences with restricted complainants. Knowledge Gap The absence of an operational definition of “living together as husband and wife” creates legal uncertainty, multiple interpretations, potential enforcement disparities, and risks of overcriminalization in citizens’ private lives. Aims This study describes the configuration of cohabitation offences in Articles 411–412, including offence elements, legal subjects, complaint mechanisms, and enforcement structure, and compares them with morality offences under the old Criminal Code. Results The findings show that cohabitation is formulated as living together as husband and wife outside legal marriage and is constructed as an absolute complaint offence, with complainants limited to husband or wife, parents, or children. The National Criminal Code expands the scope of criminalization beyond overspel in the old Criminal Code and shifts the criminal paradigm from an individualistic-colonial model to a communal-nationalistic model. Novelty This study clarifies the juridical configuration of cohabitation offences as a compromise between public morality and individual privacy. Implications Criminal law should operate as ultimum remedium through precise formulation, strict complaint limits, and proportional enforcement. Highlights • Absolute complaints restrict prosecution to parties with direct legal standing.• Broader criminalization shifts the paradigm from colonial to national values.• Ambiguous wording creates risks of uncertainty and enforcement disparity. Keywords Cohabitation Offences; Criminal Code; Absolute Complaint; Legal Certainty; Public Morality